Stipulosina new genus (Diptera: Sphaeroceridae: Limosininae) from bamboo (Chusquea scandens) stipules in Ecuador - Yau, Tiffany; Marshall, Stephen A. (Zootaxa, 2021)
The new genus Stipulosina (Sphaeroceridae: Limosininae) is described for four new species, S. amphibarba n. sp. (type species), S. barbistylus n. sp., S. ceroptistylus n. sp. and S. curvistylus n. sp., collected from bamboo stipules in the Ecuadorian Andes in 2002 and 2019. All four species are associated with stipules of the Andean bamboo Chusquea scandens Kunth but not with those of sympatric bamboo species.